Retrofit Design for Climate Resilient Housing: Strategies for Architectural Adaptation to Climate Change - Chohan, Afaq H.; Awad, Jihad; Che-Ani, Adi Irfan; Awad, Abdelaziz (Salehan Institute of Higher Education, 2025)
This study examines design flaws in single-family homes in the UAE, worsened by climate change-triggered rainfall and escalating maintenance requirements. The research focuses on three objectives: identifying existing weaknesses, analyzing building materials and construction methods, and proposing enhanced retrofit design standards. The methodology comprises both secondary data, gathered through literature reviews, and primary data obtained via site visits, participatory observation, and case studies. Examining multiple UAE regions, particularly six case studies in affected housing in Dubai, Sharjah, and Ajman, underscores widespread concerns in resilient housing, revealing deficiencies in drainage, waterproofing, and protective detailing. Notable problems include inadequate drainage slopes, subpar sealing around structural penetrations, and insufficient moisture barriers. These issues compromise structural integrity, inflate maintenance costs, and pose health hazards from mold and poor indoor air quality. By assessing current conditions, the study suggests various retrofit solutions, such as improved water-resistant coatings, slope modifications, drip edges, and overhangs. Findings emphasize rigorous detailing, robust materials, and periodic inspections to mitigate impacts from intensifying rainfall. Additionally, broader urban planning strategies, such as flood risk assessments and upgraded infrastructure, are crucial in minimizing future water intrusion. Collectively, these insights advocate novelty in research and set a blueprint for a fundamental shift in UAE housing design, prioritizing climate resilience, structural longevity, and occupant well-being in an era of rapidly changing environmental conditions. Doi: 10.28991/CEJ-2025-011-03-011 Full Text: PDF